RNAi knockdown of hPrp31 leads to an accumulation of U4/U6 di-snRNPs in Cajal bodies - Schaffert, Nina (Nature Publishing Group, 2004)
Cajal bodies (CBs) are subnuclear organelles of animal and plant cells. A role of CBs in the assembly and maturation of small nuclear ribonucleoproteins (snRNP) has been proposed but is poorly understood. Here we have addressed the question where U4/U6.U5 tri-snRNP assembly occurs in the nucleus. The U4/U6.U5 tri-snRNP is a central unit of the spliceosome and must be re-formed from its components after each round of splicing. By combining RNAi and biochemical methods, we demonstrate that, after knockdown of the U4/U6-specific hPrp31 (61 K) or the U5-specific hPrp6 (102 K) protein in HeLa cells, tri-snRNP formation is inhibited and stable U5 mono-snRNPs and U4/U6 di-snRNPs containing U4/U6 proteins and the U4/U6 recycling factor p110 accumulate. Thus, hPrp31 and hPrp6 form an essential connection between the U4/U6 and U5 snRNPs in vivo. Using fluorescence microscopy, we show that, in the absence of either hPrp31 or hPrp6, U4/U6 di-snRNPs as well as p110 accumulate in Cajal bodies. In contrast, U5 snRNPs largely remain in nucleoplasmic speckles. Our data support the idea that CBs may play a role in tri-snRNP recycling.